Practical applications of injury surveillance: a brief 25-year history of the Connecticut Injury Prevention Center. (4th January 2016) - Lapidus, Garry; Borrup, Kevin; DiVietro, Susan; Campbell, Brendan T; Beebe, Rebecca; Grasso, Damion; Rogers, Steven; Joseph, D'Andrea; Banco, Leonard
Abstract : Background: The mission of the Connecticut Injury Prevention Center (CIPC), jointly housed in Connecticut Children's Medical Center and Hartford Hospital, is to reduce unintentional injury and violence among Connecticut residents, with a special focus on translating research into injury prevention programmes and policy. The CIPC engages in four core activities: research, education and training, community outreach programmes and public policy. As surveillance is an essential element of injury prevention, the CIPC has developed a robust statewide fatal and non-fatal injury surveillance system that has guided our prior work and continues to inform our current projects. Objective: The purpose of this article is to review the projects, programmes, and collaborative relationships that have made the CIPC successful in reducing unintentional injury and violence in Connecticut throughout the course of its 25 years history. Design, setting, participants: Retrospective review of the application of injury surveillance. Results/Conclusions: We believe that the application of our surveillance system can serve as a model for others who wish to engage in collaborative, community-based, data-driven injury prevention programmes in their own communities.